A comparison of ampicillin and amoxycillin in acute on chronic bronchitis. Issue 6 (December 1979) - Anderson, G; Jariwalla, A G; Saour, J
Abstract : Twenty-five patients with an acute exacerbation of chronic bronchitis completed a double-blind trial of amoxycillin 1.5 g v ampicillin 4 g daily. After treatment for one week there was no difference between the treatments in the rates of achieving mucoid sputum, reduction in sputum volume, improvement in peak expiratory flow rate, or duration of hospital stay. In the doses studied ampicillin and amoxycillin are effective drugs of about equal cost.